2015
DOI: 10.5812/hepatmon.15(5)2015.26260
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis E Among Hemodialysis Patients: a Report From Hamadan, Iran

Abstract: Background:Previous studies have documented a high prevalence of hepatitis E among patients undergoing maintenance hemodialysis. Available studies reporting on the seroprevalence of hepatitis E in hemodialysis patients in Iran, an endemic region for the disease, are sparse.Objectives:The present study aimed to determine the prevalence rate of anti-hepatitis E antibody in hemodialysis patients in Hamadan, Iran.Patients and Methods:In this cross-sectional study, all 153 consecutive patients undergoing hemodialys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
1
9
1
Order By: Relevance
“…It may be result from the differences between source of water (26% on non-piping water in Hamedan), while all our study patients were using tap water or more hemodialysis time . (15) The main route of transmission is fecal-oral and blood was not as an important route for transmission because the virus can not cause a chronic carrier state. (16) But studies over the past decade showed the possibility of intravenous passage from person to person like hepatitis B and C virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be result from the differences between source of water (26% on non-piping water in Hamedan), while all our study patients were using tap water or more hemodialysis time . (15) The main route of transmission is fecal-oral and blood was not as an important route for transmission because the virus can not cause a chronic carrier state. (16) But studies over the past decade showed the possibility of intravenous passage from person to person like hepatitis B and C virus.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, none of the variable were not associated with increased risk of HEV-antibody positive similar to some previous studies in Iran. (15,30)…”
Section: Discussionmentioning
confidence: 99%
“…Available data, including our present results, on factors associated with anti -HEV IgG in HD patients, sex, older age, and HD duration, are inconsistent. [30][31][32][33][34] According to Mitsui et al, 30 89.7% of HD patients are HEV -infected before the HD initiation. They suggested that anti -HEV IgG positivity may persist in HD patients for years as in the general population.…”
Section: Correlates Of Anti-hepatitis E Virus Immunoglobulin Gmentioning
confidence: 99%
“…Anti -HEV IgG positivity did not correlate with a history of renal transplantation in our HD subjects, similarly as demonstrated by Psichogiou et al 31 The proportions of patients with HBV/HCV infections were comparable between HEV seropositive and seronegative HD groups, what is in concordance with the previous studies. [30][31][32][33]36 Transmission of HEV with the blood seems to be of less importance in HD patients in the era of standard administration of erythropoietin stimulating agents.…”
Section: Correlates Of Anti-hepatitis E Virus Immunoglobulin Gmentioning
confidence: 99%
“…However, independent reports showed that HEV transmission may also occur through blood transfusion [10] and from patient-to-patient through nosocomial transmission [11]. In this context, several studies reported a high prevalence of anti-HEV antibodies among hemodialysis (HD) patients suggesting that this population represents a highrisk group for this viral infection [12,13]. Nevertheless, others suggested that chronic HD is not associated with an increased risk of exposure to this virus [14,15].…”
Section: Introductionmentioning
confidence: 99%